Astrochemistry With the Orbiting Astronomical Satellite for Investigating Stellar Systems - Bergner, Jennifer B.; Shirley, Yancy L.; Jørgensen, Jes K.; McGuire, Brett; Aalto, Susanne; Anderson, Carrie M.; Chin, Gordon; Gerin, Maryvonne; Hartogh, Paul; Kim, Daewook; Leisawitz, David; Najita, Joan; et al. (Frontiers in Astronomy and Space Sciences, 2022)
Chemistry along the star- and planet-formation sequence regulates how prebiotic building blocks—carriers of the elements CHNOPS—are incorporated into nascent planetesimals and planets. Spectral line observations across the electromagnetic spectrum are needed to fully characterize interstellar CHNOPS chemistry, yet to date there are only limited astrochemical constraints at THz frequencies. Here, we highlight advances to the study of CHNOPS astrochemistry that will be possible with the Orbiting Astronomical Satellite for Investigating Stellar Systems (OASIS). OASIS is a NASA mission concept for a space-based observatory that will utilize an inflatable 14-m reflector along with a heterodyne receiver system to observe at THz frequencies with unprecedented sensitivity and angular resolution. As part of a survey of H2O and HD toward ∼100 protostellar and protoplanetary disk systems, OASIS will also obtain statistical constraints on the emission of complex organics from protostellar hot corinos and envelopes as well as light hydrides including NH3 and H2S toward protoplanetary disks. Line surveys of high-mass hot cores, protostellar outflow shocks, and prestellar cores will also leverage the unique capabilities of OASIS to probe high-excitation organics and small hydrides, as is needed to fully understand the chemistry of these objects.